Rice husk incorporated foam concrete wall panels as a thermal insulating material in buildings. Issue 5 (June 2020) - Aravind, NR; Sathyan, Dhanya; Mini, K M
The major segment for energy consumption is found in industry, transport, agricultural, residential and commercial sector. The main part of the energy consumption in residential and commercial buildings is due to the use of mechanical devices to maintain a comfortable indoor environment. Thermal conductivity of building materials is one of the factors which influence the heat transfer in buildings. Thermal conductivity can be reduced by the use of materials with low density. The present paper reports the development of a sustainable thermal insulating external wall panel and its mechanical, thermal and durability properties. The wall panel was prepared using foam concrete and rice husk and replacing the cement by fly ash. Strength of panel was tested by conducting in plane bending test and compressive strength test. Thermal conductivity was tested using guarded hot plate apparatus. Durability properties were tested by conducting water absorption test, drying shrinkage and acid resistance test. The test results showed that the rice husk and fly ash content had a major influence on the thermal conductivity and durability properties of the developed wall panels.